A SOCIOLINGUISTIC ANALYSIS OF ADDRESSING TERMS USED IN TANGLED MOVIE MANUSCRIPT - Rifai, Dian Muhammad; Prasetyaningrum, Sevian Tri (Universitas Muhammadiyah Surakarta, 2016)
This research aims at finding out the kinds of addressing terms manuscript and the reasons of using addressing terms used in Tangled Movie Manuscript. The type of this research is a descriptive qualitative research which takes a document oriented as the method of collecting data. By this method, the researchers uses Tangled movie manuscript as the data source, and the data taken are the expressions which contain addressing terms. The rate of addressing terms use first name is the biggest. Theresult of the research shows that there are five kinds namely, addressing using name (fist name, full name, and last name), addressing using intimacy, (3) addressing using kinship, (4) addressing using respect, and (5) addressing using mockery. Thestudy find seven reasons of addressing terms used in Tangled movie manuscript were showing solidarity, intimacy, mockery, power, respectful, and anger.